Design and Development of Disaster Mitigation–Based Geography Teaching Modules in the Implementation of the Merdeka Curriculum at Senior High Schools in Ambon City (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia’s position along the Pacific Ring of Fire makes it highly vulnerable to natural disasters, highlighting the urgent need to integrate disaster mitigation into school learning. Geography, as a discipline that examines Earth’s physical and human phenomena, holds strategic potential for strengthening students’ disaster awareness and preparedness, especially in high-risk regions such as Ambon. The Merdeka Curriculum provides instructional flexibility that enables the incorporation of disaster-related themes into learning processes. This study aims to design and develop a disaster-mitigation-based geography teaching module for senior high schools in Ambon City. A qualitative case study approach was employed, involving classroom observations, in-depth interviews, and document analysis to explore existing teaching practices and needs. The study producede a comprehensive design for a disaster-mitigation-integrated geography module. The findings demonstrate that integrating disaster mitigation into geography learning through a structured module enhances the relevance, applicability, and effectiveness of instruction. This research contributes to strengthening disaster-responsive geography education within the Merdeka Curriculum and supports efforts to improve student preparedness in disaster-prone areas.